Output-Specific Adaptation of Habenula-Midbrain Excitatory Synapses During Cocaine Withdrawal - Clerke, Joseph; Preston-Ferrer, Patricia; Zouridis, Ioannis S.; Tissot, Audrey; Batti, Laura; Voigt, Fabian F.; Pagès, Stephane; Burgalossi, Andrea; Mameli, Manuel (Frontiers in Synaptic Neuroscience, 2021)
Projections from the lateral habenula (LHb) control ventral tegmental area (VTA) neuronal populations’ activity and both nuclei shape the pathological behaviors emerging during cocaine withdrawal. However, it is unknown whether cocaine withdrawal modulates LHb neurotransmission onto subsets of VTA neurons that are part of distinct neuronal circuits. Here we show that, in mice, cocaine withdrawal, drives discrete and opposing synaptic adaptations at LHb inputs onto VTA neurons defined by their output synaptic connectivity. LHb axons innervate the medial aspect of VTA, release glutamate and synapse on to dopamine and non-dopamine neuronal populations. VTA neurons receiving LHb inputs project their axons to medial prefrontal cortex (mPFC), nucleus accumbens (NAc), and lateral hypothalamus (LH). While cocaine withdrawal increases glutamate release from LHb onto VTA-mPFC projectors, it reduces presynaptic release onto VTA-NAc projectors, leaving LHb synapses onto VTA-to-LH unaffected. Altogether, cocaine withdrawal promotes distinct adaptations at identified LHb-to-VTA circuits, which provide a framework for understanding the circuit basis of the negative states emerging during abstinence of drug intake.